Using tools with real and imagined tool movements - Müsseler, Jochen; Wühr, Peter; Ziessler, Michael (Frontiers in Psychology, 2014)
When using lever tools, subjects have to deal with two, not necessarily concordant effects of their motor behavior: The body-related proximal effects, like tactile sensations from the moving hand, and/or more external distal effects, like the moving effect points of the lever. As a consequence, spatial compatibility relationships between stimulus (S; at which the effect points of the lever aim at), responding hand (R) and effect point of the lever (E) play a critical role in response generation. In the present study we examine whether the occurrence of compatibility effects needs real tool movements or whether a similar response pattern can be already evoked by pure mental imaginations of the tool effects. In general, response times and errors observed with real and imagined tool movements showed a similar pattern of results, but there were also differences. With incompatible relationships and thus more difficult tasks, response times were reduced with imagined tool movements than compared with real tool movements. On the contrary, with compatible relationships and thus high overlap between proximal and distal action effects, response times were increased with imagined tool movements. Results are only in parts consistent with the ideomotor theory of motor control.